Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11605-017-3543-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Pancreaticoduodenectomy: a NSQIP Analysis

Abstract: Background An increasing body of literature is supporting the safety of minimally invasive pancreaticoduodenectomy compared to open pancreaticoduodenectomy, but there are limited comparative studies between laparoscopic and robotic pancreaticoduodenectomy. The aim of this study was to compare the rate of postoperative 30-day overall complications between laparoscopic and robotic pancreaticoduodenectomy. Methods Patients who underwent laparoscopic and robotic pancreaticoduodenectomy were abstracted from the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 29 publications
4
50
0
1
Order By: Relevance
“…In a recent North American multicentre database study, RPS was found to be associated with a lower open conversion rate compared to LPS for both PD and DP . There was no difference in the overall morbidity rate of RPD compared to LPD . Another multicentre study from the United States demonstrated that RPD could be adopted safely with similar overall and anastomotic complications compared to the open approach even during the early learning phase .…”
Section: Discussionmentioning
confidence: 95%
“…In a recent North American multicentre database study, RPS was found to be associated with a lower open conversion rate compared to LPS for both PD and DP . There was no difference in the overall morbidity rate of RPD compared to LPD . Another multicentre study from the United States demonstrated that RPD could be adopted safely with similar overall and anastomotic complications compared to the open approach even during the early learning phase .…”
Section: Discussionmentioning
confidence: 95%
“…The review of the American College of Surgeons National Surgical Quality Improvement Program database found that the type of MIPD (laparoscopic or robotic) was not associated with postoperative complications [53]. Another similar study from Zimmerman et al found that robotic surgery was less frequently performed for malignancies and was associated with more surgical site infections, but a lower conversion rate compared with laparoscopy [54].…”
Section: Laparoscopic Versus Robotic Pancreatoduodenectomymentioning
confidence: 99%
“…Ein Review des American College of Surgeons National Surgical Quality Improvement Program (NSQIP) zeigt, dass weder die laparoskopische noch auch die robotisch assistierte Pankreatoduodenektomie mit einer erhöhten Rate an postoperativen Komplikationen einhergehen [21].…”
Section: Aufbau Der Robotisch Assistierten Pankreaschirurgieunclassified